Digital public goods platforms for development: The challenge of scaling. Issue 5 (28th September 2022) - Nicholson, Brian; Nielsen, Petter; Sahay, Sundeep; Sæbø, Johan Ivar
Abstract: In this article we consider the notion of digital global public good and articulate our understanding of it. Against this conceptual foil, we examine the development of DHIS2, a global health platform inspired by public goods, focusing on the paradoxes that arise in the scaling process. We find that the scaling dynamics played out differently at the macro and micro levels, giving rise to the following paradoxes: addition of new functionalities to cater to the universe of users across the world (macro level) works counter to the needs of users in particular locations (micro level); responsiveness to the requests of the donors with a global view (macro level) distorts the production process, as the voices of users, situated in remote locations in developing countries, are not adequately heard; the system needs to be simultaneously relevant across the global (macro level) and the local (micro level), when the former calls for decontextualization and the later (re)contextualization. We then discuss challenges these paradoxes create with regard to attaining non-rivalry and non-exclusion, the defining characteristics of a public good.